Penggunaan Media Pembelajaran dalam Meningkatkan Literasi Baca Tulis Siswa SDN 1 Nagritengah - Herdiana Sastranegara; Wiwi Kurnia; Suharyanto H. Soro; Ida Tejawiani (Global Education Journal, 2026)
This study was motivated by the importance of instructional media in improving elementary school students' reading and writing literacy skills. The purpose of this study was to describe the use of storybooks and Student Worksheets (LKPD) as instructional media to improve the reading and writing literacy of second-grade students at SDN 1 Nagritengah, including the implementation process, students' responses, contributions to literacy development, and the supporting and inhibiting factors. This study employed a qualitative approach using a descriptive method. The research subject consisted of one second-grade student at SDN 1 Nagritengah who had limited reading ability. Data were collected through observation, semi-structured interviews, and documentation. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data collection, data reduction, data display, and conclusion drawing and verification. Data credibility was ensured through source, technique, and time triangulation. The findings revealed that the use of storybooks and Student Worksheets (LKPD) had a positive impact on improving students' reading and writing literacy. These instructional media increased students' interest in reading, improved reading comprehension, enriched vocabulary, enhanced their ability to retell stories, and increased their self-confidence in reading activities. Supporting factors included teachers' creativity in selecting instructional media, the availability of attractive storybooks, and students' enthusiasm during learning. Meanwhile, the main obstacle was students' limited vocabulary. Therefore, the use of storybooks and Student Worksheets (LKPD) can serve as an effective instructional strategy to support the School Literacy Movement (GLS) and improve elementary school students' reading and writing literacy skills.